La factorización a través del álgebra geométrica. Experiencia de enseñanza aprendizaje con estudiantes de grado octavo. - López Pinzón, William Alberto (Universidad Antonio Nariño, 2023)
This monograph was born from the reflection of the teaching task, when approaching the concept of algebraic factoring with students. Therefore, in the search to strengthen this process, the design of a didactic strategy to teach factoring from the algebra-geometry relationship was proposed. These two thoughts as mediators in the didactic guides under the pedagogical model Concrete, Pictorial and Symbolic (COPISI) based on Moreira's (2005) theory of critical meaningful learning.